El juego para fortalecer la equidad de género en los niños de educación inicial subnivel 2 de la Unidad Educativa Fiscomisional de Fuerzas Armadas, Colegio militar Nro. 6 combatientes de Tapi, ciudad de Riobamba - Santos Villalva, Grace Damaris (2025)
The present research aimed to determine the use of play to strengthen gender equity in the Initial Education Level 2 at the Fiscomisional Educational Unit of the Armed Forces, Military School No. 6 “Combatientes de Tapi,” in the city of Riobamba. It is recognized that in early childhood education, play plays an essential role, as it promotes values such as equality, respect, and diversity, contributing to the integral development of boys and girls and to the elimination of gender stereotypes that may limit their personal and social growth. Methodologically, the research was conducted using a mixed approach—qualitative and quantitative—combining field data collection with a documentary analysis of various bibliographic sources to support the theoretical framework. The design was non-experimental and cross-sectional, employing analytical and descriptive methods. The study population consisted of 20 children from Initial Level 2. For data collection, observation sheets were applied—one directed at the children and another at the teacher—which allowed for a detailed analysis of practices related to the use of play and its influence on gender equity. The main findings indicated that play fosters children’s emotional, social, physical, and intellectual development, strengthens their self-esteem and self-concept, and simultaneously contributes to reducing stereotypes and discriminatory attitudes. Finally, conclusions and recommendations are presented to strengthen the use of play as a tool to promote gender equity and respect for individual differences in the classroom.